Characterization of X-ray flare properties of AB Dor. Issue Volume 11:Issue S320(2015) (9th September 2016) - Lalitha, S.
Abstract: The strong similarities between the flares observed on the Sun and in low mass stars has raised question regarding dynamo in these stars. Using the Sun as a prototype, one may be able to address this. In this paper, we present an analysis of 30 intense X-ray flares observed from AB Dor. These flares detected in XMM-Newton data show a rapid rise (500-3000 s) and a slow decay (1000-6000 s). Our studies suggest that the scaling law between the flare peak emission measure and the flare peak temperature for all the flares observed on AB Dor is very similar to the relationship followed by solar flares. Furthermore, we obtain the frequency distribution of flare energies which is a crucial diagnostic to calculate the overall energy residing in a flare. Our results of this study indicate that the large flare (10 33 ≤ E ≤ 10 34 erg) may not contribute to the heating of the corona.